2017
DOI: 10.7251/gsf1421025s
|View full text |Cite
|
Sign up to set email alerts
|

FITOCENOLOŠKA ANALIZA MEZOFILNIH ŠUMA PITOMOG KESTENA (Castanea sativa Mill.) U OKOLINI KOSTAJNICE (BOSNA I HERCEGOVINA)

Abstract: Apstrakt: U radu je prikazana fitocenološka analiza mezofilnih šuma pitomog kestena (Castanea sativa Mill.) u Privrednoj jedinici "Pastirevo" kod Kostajnice. Istraživane sastojine su degradirane, izdana kog porijekla. Floristi ka analiza je pokazala da pripadaju mezofilnoj asocijaciji Aposeri foetidae-Castaneetum sativae Medak 2011 sveze Aremonio-Fagion i to njenoj degradiranoj varijanti var. Rubus hirtus. Ovaj osnovni tip se dalje raš lanjuje na mezofilniju varijantu bez kitnjaka (subasocijacija typicum) i ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…By comparing palynological profiles of polyfloral samples with other research (Ramos et al, 2002;Sabo et al, 2011;Pupuleku et al, 2016;Rašić, Štefanić, Antunović, Jović & Kristek, 2018;Temizer et al, 2018) similarities are observed in terms of varying the share of chestnut as a honey plant, in the interval from 3 to 40%. So far, chestnut research in Bosnia and Herzegovina has mainly focused on its ecological and synecological differentiation (Sučić, 1953a(Sučić, , 1953bGlišić, 1954;Wraber, 1958;Macanović, 2011;Stupar, Šurlan, Travar & Cvjetičanin, 2014), morphological characteristics (Mujić et al, 2010;Mujagić-Pašić & Ballian, 2011), chemical composition (Mujić, Alibabić, Ibrahimpašić, Jahić & Muslimović, 2006) and diseases (Treštić, Dautbašić & Mujezinović, 2009). This paper represents original research in the context of defining the potential of chestnut as a honey-bearing plant in the flora of Bosnia and Herzegovina.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By comparing palynological profiles of polyfloral samples with other research (Ramos et al, 2002;Sabo et al, 2011;Pupuleku et al, 2016;Rašić, Štefanić, Antunović, Jović & Kristek, 2018;Temizer et al, 2018) similarities are observed in terms of varying the share of chestnut as a honey plant, in the interval from 3 to 40%. So far, chestnut research in Bosnia and Herzegovina has mainly focused on its ecological and synecological differentiation (Sučić, 1953a(Sučić, , 1953bGlišić, 1954;Wraber, 1958;Macanović, 2011;Stupar, Šurlan, Travar & Cvjetičanin, 2014), morphological characteristics (Mujić et al, 2010;Mujagić-Pašić & Ballian, 2011), chemical composition (Mujić, Alibabić, Ibrahimpašić, Jahić & Muslimović, 2006) and diseases (Treštić, Dautbašić & Mujezinović, 2009). This paper represents original research in the context of defining the potential of chestnut as a honey-bearing plant in the flora of Bosnia and Herzegovina.…”
Section: Discussionmentioning
confidence: 99%
“…The distribution of chestnut forests in Bosnia and Herzegovina is conditioned by the geological and pedological peculiarities of the area, and is limited to only three areas: the Neretva area in Herzegovina (the vicinity of Jablanica, Konjic and Prozor), where it builds communities Castanetum sativae hercegovinicum; north-eastern Bosnian area (surroundings of Srebrenica, Bratunac, Zvornik and Tuzla) where it makes communities Castaneo-Fagetum submontanum; and it has the broadest distribution in the area of Bosnian Krajina (surroundings of Cazin, Kladuša, Bosanska Krupa, Novi Grad, Dubica, Kostajnica, Gradiška, Laktaš, etc.) where it forms communities of Querco-Castanetum sativae (Glišić, 1954;Wraber, 1958;Stupar, Šurlan, Travar & Cvjetičanin, 2014;Milanović, Brujić, Đug, Muratović & Lukuć Bilela, 2015).…”
Section: Introductionmentioning
confidence: 99%